Body composition in professional football players: A method comparison - Brinkmans, N. Y. J.; van Loon, L. J. C.; van Dijk, J. W. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Body composition is routinely monitored in most professional football players. Dual-energy X-ray absorptiometry (DXA) is generally accepted as a reliable method to monitor body composition, although consensus on the preferred analysis algorithm is absent. Furthermore, DXA is expensive and often not feasible for regular monitoring. Standardised skinfold measurements may be a valuable instrument for regular monitoring of body composition, although information on the agreement between skinfold measurements and DXA is lacking. Therefore, we assessed the association and agreement between body fat percentage derived from DXA, deuterium dilution (DD) and skinfold thickness. Fifty-eight professional male football players from 3 first team squads playing in the Dutch Eredivisie were included. Fat mass (FM) and fat free mass (FFM) were assessed by a whole-body DXA scan and analysed with the classic (DXAC) and NHANES (DXAN) algorithm. Fat mass was also derived from total body water as assessed by DD (n=45). Skinfold thickness (8 sites) was assessed according to ISAK standards and translated to body fat % (BF%) by Juhasz and Durnin & Womersly (D&W) equations. Associations between methods were analysed by Pearson`s correlation coefficient. Bland-Altman plots were made to assess the agreement between different methods. Mean BF% by DXAC, DXAN, DD, Juhasz and D&W were respectively 11.2±1.9, 15.7±1.8, 11.7±2.4, 7.0±1.0 and 11.2±2.5 %. The sum of 8 skinfolds (SF) was 54.8±13.1 mm. Despite the relatively small data range, DXAN, DD, Juhasz, D&W and sum of 8 SF correlated strongly with BF% derived from DXAC (r=1.00; r=0.85; r=79; r=72; r=0.81, respectively). Despite the perfect correlation, BF% derived from DXAN was systematically higher (+4.6±0.1%) than DXAC, whereas DD showed an acceptable level of agreement with DXAC (+0.7±1.3%). Large proportional bias in BF% was observed with the Juhasz equation when compared with DXAC. In conclusion, the high level of agreement between DD and DXAC supports the use of the DXAC analysis algorithm for professional football players. Furthermore, our data suggest that the sum of 8 SF is the most appropriate skinfold-based approach to monitor body fat in professional football players.